TRANSFORMASI PENDIDIKAN ORANG DEWASA DIERA DIGITAL (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Adult education in the digital era faces significant challenges and opportunities. With the rapid development of information and communication technology (ICT), the adult education system is undergoing a transformation, utilizing various digital platforms such as e-learning, educational apps, and social media. This study aims to explore the role of technology in adult education, particularly in the context of distance learning, digital divides, digital literacy, effective learning models, and policies necessary to maximize the potential of digital education. Technology has provided broader access for adults to obtain education relevant to their needs, although a digital divide still exists that hampers some individuals, especially in underserved areas. Distance learning offers essential flexibility for adult learners, but it requires strong digital literacy to fully utilize the available technology. Therefore, adult education must integrate digital literacy skills and experiential learning models that are relevant to their practical needs. This study also suggests the importance of policies supporting equitable access and improving digital literacy quality across different communities, to ensure that digital education is accessible to all adults in Indonesia.